ARGUMENTATION OF SENIOR HIGH SCHOOL STUDENTS ON PHYSICS INSTRUCTION BASED INQUIRY - Imaniar, Berliana Oni; Supeno, Supeno; Lesmono, Albertus Djoko (Prodi Pendidikan Fisika Universitas Sarjanawiyata Tamansiswa, 2020)
Argumentation as the one of important skills must be included in the science learning. With argumentation skills, students can show their opinion include evidence and justification logically. Argumentation is important for students, but it seldom integrate in physic learning based inquiry. Participation of students who decrease in the learning can influence to argumentation’s ability of students. Physic learning based inquiry which include argumentation section can grow up the action students to give argumentation. Component of argumentation’s ability are evidence and justification for argument, counter argument, and rebuttal. This research is conduct for three meetings on the fluid static’s chapter in Senior High School of one Gambiran. Students’ argumentation skills measure from argumentation section and students’ worksheets has consisted component’s of argumentation. Purpose of this research is describe of students’ argumentation skills on physics instruction based inquiry. Result of this research is shown that students’ argumentation skills increase on last meeting of physics instruction. Participation of students give argumentation influenced by topic of the problems. Keywords: argumentation, participation, inquiry, physic, learning